The form of host density-dependence and the likelihood of host-pathogen cycles in forest-insect systems - Liu, W; Bonsall, M; Godfray, H (Elsevier, 2007)
Forest-insect systems frequently show cyclic dynamics which has been of considerable interest to both experimental and theoretical ecologists. One important issue has been the manner in which density-dependence acting on the host population through resource competition influences the likelihood of population cycles. Existing models make contradictory predictions. Here, we explore two models that allow different forms of density-dependence to be examined. We find that host density-dependence can influence the persistence of the host-pathogen interaction, the likelihood of population cycles and the stability of the host-pathogen interaction. In particular, over-compensatory density-dependence is likely to lead to host-pathogen cycles while under-compensatory density-dependence can promote stability. We discuss these differences with reference to the different forms of intraspecific competition and recent developments in insect population ecology.